Knock-down of oncohistone H3F3A-G34W counteracts the neoplastic phenotype of giant cell tumor of bone derived stromal cells - Fellenberg, Jörg; Sähr, Heiner; Mancarella, D.; Plass, C.; Lindroth, A. M.; Westhauser, Fabian; Lehner, Burkhard; Ewerbeck, Volker (Cancer letters, 2019)
Giant cell tumors of bone (GCTB) are semi-malignant tumors associated with extensive osteolytic defects and massive bone destructions. They display a locally aggressive behavior and a very high recurrence rate. Recently, a single mutation has been identified in GCTB affecting the H3F3A gene coding for the histone variant H3.3 (H3.3-G34W). The aim of this study was to investigate whether H3.3-G34W is sufficient to drive tumorigenesis in GCTB. Initially, we confirmed the high frequency of this mutation in 94% of 84 analyzed tissue samples. Using a siRNA based approach we could selectively knockdown H3.3-G34W in primary neoplastic stromal cells isolated from tumor tissue (GCTSC). H3.3-G34W knockdown caused a significant inhibition of cell proliferation, migration and colony formation capacity in vitro. Xenotransplantation of GCTSCs onto the chorioallantoic membrane of fertilized chicken eggs further demonstrated a significant impact of H3.3-G34W knockdown on tumor engraftment and growth in vivo. Our data indicate that H3.3-G34W is sufficient to drive tumorigenesis in GCTB. Apart from the application of H3.3-G34W screening as diagnostic tool, our data suggest that H3.3-G4W represents a promising target for the development of new GCTB therapies.
Gesehen am 09.07.2019